Investing in Eastern Europe / Capitalizing on Emerging Markets - Paliwoda Stanley (Allyn And Bacon, 1995)
This book identifies investment opportunities in specific industry sectors, and offers timely insights into how the individual markets will fare in the future. Preface, Executive Summary, Introduction, Investing in a Changed Eastern Europe: The Evolution of Joint Ventures, Reasons for Investing in Eastern Europe, Eastern European Expectations of Foreign Investment, Deciding on an Investment Strategy, Choosing the Best Investment Form, Negotiating a Joint Venture or Acquisition, Privatization and Liquidation Sales, The Czech Republic, Slovakia, Hungary, Poland, Albania, Bulgaria, Romania, The Future?, Index.